An exploration of the motivation and opportunity seeking behaviours of social entrepreneurs in Cape Town - Chirinda, Nyarai Theresa Faith (Department of Social Development, 2014)
This research study of the motivation and opportunity-seeking behaviours of social entrepreneurs in Cape Town was conducted among fifteen social entrepreneurial organisations in Cape Town during the months of June, July and August 2010. The results of this qualitative research show that there are various factors that motivate people to become social entrepreneurs, such as the desire to make a difference in other peoples? lives and provide innovative solutions to existing social problems.